2023
DOI: 10.1186/s40478-022-01497-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between hypertension and neurovascular inflammation in both normal-appearing white matter and white matter hyperintensities

Abstract: The major vascular cause of dementia is cerebral small vessel disease (SVD), including white matter hyperintensities (WMH) amongst others. While the underlying pathology of SVD remains unclear, chronic hypertension and neuroinflammation are recognized as important risk factors for SVD and for the conversion of normal-appearing white matter (NAWM) to WMH. Unfortunately, most studies investigating the role of neuroinflammation in WMH relied on peripheral blood markers, e.g., markers for systemic or vascular infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…spontaneously hypertensive rats or angiotensin II-induced hypertensive mice) and particularly in the human brain of hypertensive individuals to generalize the concept and rule out genetic contributions in the SHRSP model [16, 69]. Lastly the integration of our results into human literature remains difficult since longitudinal studies on an individual bases are sparse [5, 13] and neuropathological studies often address advanced and end-stages of the disease [128]. This conflict can be overcome if future research focuses on characterizing the silent phase of hypertension, before structural pathologies occur.…”
Section: Discussionmentioning
confidence: 99%
“…spontaneously hypertensive rats or angiotensin II-induced hypertensive mice) and particularly in the human brain of hypertensive individuals to generalize the concept and rule out genetic contributions in the SHRSP model [16, 69]. Lastly the integration of our results into human literature remains difficult since longitudinal studies on an individual bases are sparse [5, 13] and neuropathological studies often address advanced and end-stages of the disease [128]. This conflict can be overcome if future research focuses on characterizing the silent phase of hypertension, before structural pathologies occur.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has indicated that BCAA can initiate inflammation and oxidative stress in endothelial cells and the vasculature, which may lead to endothelial dysfunction and potentially contribute to cardiovascular disease [ 114 ]. Future studies should include additional markers of (vascular) inflammation (e.g., GFAP) to provide a more complete understanding of the underlying mechanisms of neuroinflammation and how it is affected by exercise and BCAA [ 12 ]. For example, GFAP expression has been shown to increase in astrocytes in response to inflammation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should include additional markers of (vascular) inflammation (e.g., GFAP) to provide a more complete understanding of the underlying mechanisms of neuroinflammation and how it is affected by exercise and BCAA [ 12 ]. For example, GFAP expression has been shown to increase in astrocytes in response to inflammation [ 12 ]. In this study, the BCAA-supplemented exercise-treated mice behaved similarly to the HFD-fed mice with respect to the majority of neuroimaging parameters assessed, possibly because BCAA reversed exercise-induced beneficial effects on the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3E). Indeed, neurovascular inflammation is involved in the aetiology of WMH [258]. Similarly, cerebral small vessel disease has been identified as a key hallmark of a broad range of neurodegenerative conditions.…”
Section: Microvascular Inflammation Across the Age-related Diseases C...mentioning
confidence: 99%